Experience with a Massive Open Online Course in Rural Rwanda - Warugaba, Christine; Naughton, Brienna; Hedt-Gauthier, Bethany; Muhirwa, Ernest; Amoroso, Cheryl L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The growing utilization of massive open online courses (MOOCs) is opening opportunities for students worldwide, but the completion rate for MOOCs is low (Liyanagunawardena, Adams, & Williams, 2013). Partners In Health (PIH) implemented a “flipped” MOOC in Rwanda that incorporated in-class sessions to facilitate participant completion. In October 2013, PIH invited its employees, as well as those at the Ministry of Health, to participate in an online MOOC. Each site had at least one volunteer facilitator who accompanied participants throughout the course by providing course materials and facilitating the understanding of the online material during the weekly class sessions. Following the conclusion of the course, all participants were asked to complete an online survey. A total of 38 out of 62 registered participants completed the survey and of these 38 participants, 20 (52.6%) successfully finished the course. The number of in-person sessions attended was significantly associated with course completion (p < 0.05), and 85% who successfully completed the course attended at least three of seven sessions. Sixteen (80%) participants believed that the completion of this course would help them with career advancement. Half of the participants (19 of 38, 50%) were employed with a position related to research. Other job titles included the following: nurses (4 of 38, 10.5%), a pharmacist (1 of 38, 2.6%), a clinical psychologist (1 of 38, 2.6%), a dentist (1 of 38, 2.6%), and others (10 of 38, 26.3%). The job title was not significantly related to course completion. Our experience, with a completion rate of over 50%, yields several lessons for incorporating MOOCs into capacity-building programs to leverage the potential of online learning in resource-limited areas.